The village school teachers in Kantaralak district, Srisaket province, Thailand - Chejtapun, Prasert 1941- (s.n], 1971)
The characteristics and working conditions of the village school teachers in Kantaralak District, Srisaket Province, Thailand in the school year 1970-1971 was determined. The normative survey method was used with the questionnaire as the research tool. A picture may be drawn based on the characteristics of the village school teachers.